(untitled) (Revista Educação, Artes e Inclusão, 2024)
It’s apparently nonsense to ponder the construction of images for people with visual impairments, especially when such subjects are the authors of the imagery production. Against this idea, we present some results of the university extension project A Fotografia e Sentir. The actions involving teaching and photographic practice with students from IEACN - Institute of Education and Assistance to the Blind of the Northeast, located in the city of Campina Grande – Paraíba (Brazil). The text proposes a debate on didactic and methodological resources with a focus on accessibility and inclusion, the use of multisensoriality for the construction of imagery when exploring auditory and tactile stimuli, as also the importance of providing the role of emitter and creative source to the visually impaired student. We aim to encourage autonomous subjects and builders of their own knowledge, therefore, we present an experience report on the development of autonomy and photographic perception of students with visual impairment, that, by producing images, stimulated body awareness and explored their perceptions, indicating the process as possible methodological approach to inclusive photographic technique. The theoretical path involved Barbosa (1999, 2007), Vygotsky (1997), Schafer (2003), Merleau-Ponty (1994), Alves (2009) among others.